11-{[2-(3-Fluorophenyl)ethyl](methyl)amino}pentacyclo[5.4.0.0(2,6).0(3,10).0(5,9)]undecan-8-one - Banister, Samuel D. (International Union of Crystallography, 2010)
In the title compound, C(20)H(22)FNO, the distances close to the carbonyl and amine are: N—O = 3.232 (4) Å and N—C = 2.666 (5) Å. The crystal packing is unremarkable.